1997
DOI: 10.1071/mf97170
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis and ovarian development cycle of the spiny lobster Panulirus japonicus (Decapoda:Palinuridae)

Abstract: Oogenesis and ovarian development in female Panulirus japonicus were examined by light and electron microscopy. Eight substages (oogonium, bouquet, chromatin nucleolus, oil globule, pre-yolk platelet, yolk platelet, pre-maturation and maturation) were distinguished in the typical process of oogenesis (multiplication, pre-vitellogenesis, vitellogenesis and maturation stages). Yolk accumulation started at the late pre-yolk platelet substage, when electron-dense granules appeared. Yolk granules seemed to be accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 0 publications
7
30
0
Order By: Relevance
“…This supports findings of the highly conservative of the process of oogenesis in the family Euphausiacea (Kikuno and Kawamura, 1983;Cuzin-Roudy, 1987b, 1993, 1997aCuzin-Roudy and Amsler, 1991;Cuzin-Roudy and Buchholz, 1999) for Meganyctiphanes norvegica and Euphausia superba. We did not directly adopt classifications developed by Cuzin-Roudy (1993) and Cuzin-Roudy and Buchholz (1999) because Minagawa and Sano (1997), using transmission electron microscopy in their gonad classification based on the work of Yano (1988), developed a classification that seems to be more specific because it distinguished morphological differences between oil globule and yolk granules in decapods. Although we were not able to observe all of the substages of this gonad classification, using resinembedded gonads stained with black sudan, we observed that N. simplex oocytes Oc3 had small oil glubules in the ooplasm during early vitellogenesis (endogenous), which was not previously observed in other euphausiids (Cuzin-Roudy and Amsler, 1991;Cuzin-Roudy and Buchholz, 1999).…”
Section: Gonad Developmentmentioning
confidence: 99%
“…This supports findings of the highly conservative of the process of oogenesis in the family Euphausiacea (Kikuno and Kawamura, 1983;Cuzin-Roudy, 1987b, 1993, 1997aCuzin-Roudy and Amsler, 1991;Cuzin-Roudy and Buchholz, 1999) for Meganyctiphanes norvegica and Euphausia superba. We did not directly adopt classifications developed by Cuzin-Roudy (1993) and Cuzin-Roudy and Buchholz (1999) because Minagawa and Sano (1997), using transmission electron microscopy in their gonad classification based on the work of Yano (1988), developed a classification that seems to be more specific because it distinguished morphological differences between oil globule and yolk granules in decapods. Although we were not able to observe all of the substages of this gonad classification, using resinembedded gonads stained with black sudan, we observed that N. simplex oocytes Oc3 had small oil glubules in the ooplasm during early vitellogenesis (endogenous), which was not previously observed in other euphausiids (Cuzin-Roudy and Amsler, 1991;Cuzin-Roudy and Buchholz, 1999).…”
Section: Gonad Developmentmentioning
confidence: 99%
“…Some spiny lobsters are known to produce multiple broods, where the ovaries mature whilst the female is ovigerous (Minagawa & Sano, 1997). In the present study all of the ovigerous females possessed spent ovaries, including mid and late stage ovigerous females.…”
Section: Discussionmentioning
confidence: 53%
“…Mitosis mainly occurs in immature oocytes, while the mature oocytes are found in the metaphase of the first meiosis. This phenomenon indicates that the first meiosis occurs at maturation stage, and the second meiosis is completed after spawning (Yano, 1988;Minagawa and Sano, 1997;Zhu et al, 2005a). There is evidence that female E. carinicauda have the potential to carry more than one batch of eggs within a reproductive period.…”
Section: Discussionmentioning
confidence: 99%